Implementasi Lean Management Dalam Meningkatkan Efisiensi Operasional Di PT Niaga Sejahtera Plastik Industri - Novitasari, Ratih; Nurhidayah, Nurhidayah; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the implementation of Lean Management in improving operational efficiency at PT Niaga Sejahtera Plastik Industri. Lean Management focuses on eliminating waste to create a lean process. The study used a qualitative descriptive approach through interviews, observations, and documentation. The results show that the implementation of 5S, Kaizen, Kanban, VSM, and JIT can reduce production process time, reduce defect rates, and increase productivity. Lean Management has been proven effective in improving the company's operational efficiency. Keywords: Lean Management, Operational Efficiency, Waste, Kaizen, VSM